Factors in Variability of Serial Gabapentin Concentrations in Elderly Patients with Epilepsy. Issue 10 (19th September 2017) - Conway, Jeannine M.; Eberly, Lynn E.; Collins, Joseph F.; Macias, Flavia M.; Ramsay, R. Eugene; Leppik, Ilo E.; Birnbaum, Angela K.
Abstract : Objectives: To characterize and quantify the variability of serial gabapentin concentrations in elderly patients with epilepsy. Methods: This study included 83 patients (age ≥ 60 yrs) from an 18‐center randomized double‐blind double‐dummy parallel study from the Veterans Affairs Cooperative 428 Study. All patients were taking 1500 mg/day gabapentin. Within‐person coefficient of variation (CV) in gabapentin concentrations, measured weekly to bimonthly for up to 52 weeks, then quarterly, was computed. Impact of patient characteristics on gabapentin concentrations (linear mixed model) and CV (linear regression) were estimated. Results: A total of 482 gabapentin concentration measurements were available for analysis. Gabapentin concentrations and intrapatient CVs ranged from 0.5 to 22.6 μg/ml (mean 7.9 μg/ml, standard deviation [SD] 4.1 μg/ml) and 2% to 79% (mean 27.9%, SD 15.3%), respectively, across all visits. Intrapatient CV was higher by 7.3% for those with a body mass index of ≥ 30 kg/m 2 (coefficient = 7.3, p=0.04). CVs were on average 0.5% higher for each 1‐unit higher CV in creatinine clearance (coefficient = 0.5, p=0.03) and 1.2% higher for each 1‐hour longer mean time after dose (coefficient = 1.2, p=0.04). Conclusions: Substantial intrapatient variability in serial gabapentin concentration was noted in elderly patients with epilepsy. Creatinine clearance, time of sampling relative to dose, and obesity were found to be positively associated with variability.